The Relationship Between Physical Activity and Fruit and Vegetable Consumption Habits and Obesity in College Students in Papua Province - Ayomi, Mina Blandina; Sitorus, Rena Fadila Siska; Mamoribo, Sherly Novita; Irmanto, Maxsi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Obesity is a growing health problem, including among university students. The Indonesian government, through the Healthy Living Community Movement (GERMAS), promotes healthy lifestyles as a preventative measure against non-communicable diseases, including obesity. This study aims to determine the relationship between physical activity, fruit and vegetable consumption, and the incidence of obesity among university students in Papua Province. Methods: This study used a quantitative approach with a cross-sectional design. The respondents were 127 university students studying in Jayapura City, selected using proportionate stratified random sampling. Data were collected using questionnaires and Body Mass Index (BMI) measurements, and analyzed using the Chi-Square test. Results: The results of the study showed a significant relationship between physical activity (p = 0.028, < 0.05) with a relative risk (RP) value of 3.119, and fruit and vegetable consumption (p = 0.005, < 0.05) with an RP value of 3.160, in relation to obesity. Activities within the Healthy Living Community Movement are mandatory for students as a form of prevention against non-communicable diseases. The movement, which encourages physical activity and the consumption of fruits and vegetables, should be implemented as a regular program at both public and private universities in Papua Province. University leaders in charge of student affairs are required to allocate regular funds to support this initiative.